OPTIMIZATION OF DIAGNOSIS AND TREATMENT OF HIVINFECTED PATIENTS WITH RENAL PATHOLOGY (World Bulletin of Public Health, 2025)
The review analyzes the prevalence, pathogenesis, diagnosis, and treatment of HIV infection. The main clinical and morphological variants of kidney involvement in HIV infection are presented. The prevalence of kidney damage in HIV infection ranges from 20% to 30% and includes clinical and morphological variants such as HIV-associated nephropathy (HIVAN), immune complex HIV-associated kidney disease, and thrombotic microangiopathy. In individuals with HIV infection who are not receiving antiretroviral therapy (ART), the most common type of kidney disease is HIVAN.